Development of sound system level tools “SoQMeT” / Muhammad Danial bin Abu Hanafiah ... [et al.] - Abu Hanafiah, Muhammad Danial; Mohamad Yaziz, Muhammad Aleef; Mohd Sazali, Muhammad Aiqal; Ainun Musir, Adhilla; Abdul Karim, Nurulzatushima; Hasan, Daliah (2021)
Noise level of sound system is needed to comply and achieve the minimum recommendations of Malaysia Standard. The objective of this project is producing the SoQMeT which is an Excel basis system. The SoQMeT is developed to provide instant and easy monitoring tools of noise level. The scope areas of the measurement of noise level were at various places in the building and also infrastructures. The noise levels for the selected places were obtained and the result was analyzed by using the SoQMeT in order to comply with the Malaysian Recommendation Standard. The colour zoning of low, moderate and high of noise level are shown in SoQMeT. As the result, there are places complying with the standard and some places failed to follow the minimum recommendation level. Result obtained from this project, there are several places that need to give attention and do fast correction action and maintenance especially for walkways and waiting areas for a better hearing comfort to the people. The noise level for these places was considered high and exceeds the minimum requirement of the standard.